PELATIHAN RESUSITASI JANTUNG PARU (RJP) BAGI APARAT PEMERINTAH, KADER KESEHATAN DAN MASYARAKAT DI DESA SANROBONE KABUPATEN TAKALAR - Sudarman Sudarman; Akbar Asfar (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this community service activity is to improve the knowledge and skills of the government, health cadres, and the community in Sanrobone Village, Takalar District, about pulmonary resuscitation (CPR) of at least 90% can help first aid in cardiac arrest and respiratory arrest. The results of community service are government officials, health cadres, and the community has been able to determine clinical and biological death, how to cope with cardiac arrest and respiratory arrest, understanding, goals, and indications of CPR. Participants have also taken procedural RJP to pay attention to the danger/safety of the helper, the environment, and the victim. Participants can provide sound stimulation and victims to the victim, fig asking for help, checking the pulse and checking to breathe, placing at the massage site giving breath-to-mouth relief and mouth to cover and provide recovery positions (recover ).